Pendekatan Prosesual: Menjawab Tantangan dalam Mengkaji Dinamika Budaya - Yunita T. Winarto (Antropologi Indonesia, 1999)
Non-processual approaches in anthropology have been heavily criticized for not providing an adequate framework for explaining the emergence of socio-cultural phenomena, and the processes and mechanisms of change. Socio-cultural life is undeniably dynamic and everchanging. In facing this matter many anthropologists have turned to a processual approach in studying the dynamics of culture in the last two decades. In this article the author shows how the processual approach is applied to the study of cultural dynamics. The author begins by discussing the unit of analysis and focus of study in a processual approach. Following that, she discusses the implication of this upon the methods and strategies for uncovering, describing and explaining change. The author also shows how this approach can uncover the heterogeneous nature of a socio-cultural phenomenon and the extent to which that heterogeneity allows change to occur. Her arguments are based upon empirical cases of knowledge transmission and formation among farmers in several locations on the north coast of West Java and Central Lampung.